Penerapan Ekohidraulik pada Hulu Sub DAS Bompon, Kabupaten Magelang, Jawa Tengah - Maola Maqdan; Andi Sungkowo; Ekha Yogafanny (Jurnal Ilmiah Lingkungan Kebumian, 2019)
The upstream of Bompon sub-watershed is located in Magelang Regency, Central Java. The movement of soil mass and erosion often happens at Bompon sub-watershed. The occurrence of erosion is caused by high runoff so the soil and rocks become eroded and the loose material will enter the river body. The purpose of this study is to determine the characteristics and application of eco-hydraulics in the Upper Bompon watershed. The methods used include survey, mapping methods and mathematical methods. Preparation stage were done by collecting secondary data which were used as the basis for field data collection. The field work phase include collecting primary data by crosschecking and mapping. Furthermore, measuring river flow and observing the name of the flora. The results of the study showed that the width of the river was 1.1 m, the same as rice field irrigation channel with the pattern of dendritic drainage. The highest river flow discharge was 0.043 m3/s that occur in January, while the lowest was in June with river discharge of 0.010 m3/s. Eco-hydraulic application uses cliff restraint methods, namely cliff planting, cliff cover, cliff plants, flat fences and the use of gulud terraces. Keywords: River Flow Discharge, Ecohydraulic, Erosion, Upstream.